Who wears The Jacket?. Issue 2 (1st October 2017) - Maggio, Rodolfo
Paul and Kaya journey through three dimensions of reciprocity: the World, the pub and their 'world'. The unmaking of their relationship suggests an underlying confrontation between incompatible gendered values. This might be interpreted as a reflection of current anthropological changes in Austria, particularly in the meaning of masculinity and femininity.